2020
DOI: 10.1155/2020/3067453
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Maintenance Intravenous Iron Therapy Can Prevent Anemia in Children with End-Stage Renal Disease Undergoing Chronic Hemodialysis

Abstract: Iron deficiency anemia is common in children with end-stage renal disease (ESRD) on long-term hemodialysis receiving erythropoiesis-stimulating agents. One approach to maintain the iron profile and hemoglobin levels is maintenance therapy with regular low doses of intravenous (IV) iron after initial iron repletion therapy; however, evidence for the benefits of this approach is lacking. This study evaluated the effect of IV iron maintenance therapy on anemia in children on regular hemodialysis. This retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 30 publications
3
17
0
1
Order By: Relevance
“…The incidence of pediatric ESRD in Indonesia is unknown at present, but data from the Indonesian Pediatrics Association indicate that 212 children with kidney failure underwent renal replacement therapy, including dialysis, in 2017 8 . A recent publication from CMH also showed that 60 pediatric cases of ESRD underwent continuous ambulatory peritoneal dialysis between 2014 and 2019, while 78 underwent chronic hemodialysis between 2015 and 2019, with kidney hypoplasia as the primary underlying disease 6,9 . However, these data likely underestimate the true prevalence of pediatric ESRD because the country has only two pediatric dialysis units located in the capital, making it extremely likely that there are many undiagnosed and untreated pediatric cases in the wider population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of pediatric ESRD in Indonesia is unknown at present, but data from the Indonesian Pediatrics Association indicate that 212 children with kidney failure underwent renal replacement therapy, including dialysis, in 2017 8 . A recent publication from CMH also showed that 60 pediatric cases of ESRD underwent continuous ambulatory peritoneal dialysis between 2014 and 2019, while 78 underwent chronic hemodialysis between 2015 and 2019, with kidney hypoplasia as the primary underlying disease 6,9 . However, these data likely underestimate the true prevalence of pediatric ESRD because the country has only two pediatric dialysis units located in the capital, making it extremely likely that there are many undiagnosed and untreated pediatric cases in the wider population.…”
Section: Discussionmentioning
confidence: 99%
“…Only Case 12 had a complication, presenting with a bleed adjacent to the graft that required further surgery within 3 hours after receiving the transplant ( 2019, with kidney hypoplasia as the primary underlying disease. 6,9 However, these data likely underestimate the true prevalence of pediatric ESRD because the country has only two pediatric dialysis units located in the capital, making it extremely likely that there are many undiagnosed and untreated pediatric cases in the wider population.…”
Section: Post-transplantation Outcomes and Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation is sometimes found in our country; as a developing country, we found constraints in resources to provide the standardized medical service. Previously, there were publications from Indonesia describing a similar challenge due to the unavailability of supporting laboratories, [20][21][22] which could require specimen transfer to laboratories outside the country and necessitated out-ofpocket expenses. As a matter of fact, the gross domestic product per capita of Indonesia in 2018 was USD $3893.60, while the cost of Harvoni© is USD $94,500 for a 12-week-treatment (in America).…”
Section: Discussionmentioning
confidence: 99%